PENGUATAN SOLIDARITAS SOSIAL KEMASYARAKAT DALAM RANGKA PEMBENTUKAN SATUAN TUGAS BENCANA DI DESA PAMONG KECAMATAN CIRUAS KABUPATEN SERANG - Abdul Apip; Rahmawati Rahmawati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2021)
Social solidarity is a relationship between individuals or groups based on moral feelings that are shared and strengthened by shared emotional experiences. Solidarity can be formed because of the same race, ethnicity or the same feelings. Social solidarity is divided into two, namely mechanical solidarity that is identical to rural communities and organic solidarity which is identical to the culture of modern society. The Covid-19 pandemic that has spread throughout the world, including Indonesia, has had a huge impact on people's lives, both from an economic, social and cultural perspective. Pamong Village is one of the villages where most of the men work as migrant workers in Jakarta. Work in the service sector as a shop assistant in trade centers such as Mangga Dua, Glodog and Tanabang, as a convention worker, as an online driver. With the Covid-19 pandemic, most workers from Pamong Village were also sent home and terminated. The problem faced by the Pamong Village community is the increasing number of families without income / vulnerable groups of people who are poor. The social solidarity that has been built in Pamong Village is still very close, where the form of routine activity carried out is the weekly recitation for both men and recitation for mothers. In addition, social solidarity is still carried out by the plerek system or the collection of rice or money that is freely collected by youths and used for social funds or compensation for families affected by disaster, illness or death, including when there are families experiencing economic difficulties.